The Influence of the School Environment on Character Students of Class IV SD Negeri 14 Buton - Nurmin Aminu; Hijrawatil Aswat; Triya Amelia; Hesti Suharsikin (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
The research objective was to determine the effect of the school environment on the character of students at SD Negeri 14 Buton. This research uses a qualitative approach with descriptive research. This type of research is qualitative research. , the aim is to describe all the components found in the study and analyze them by collecting data using observation, interview and documentation techniques. Data analysis used analytical techniques (data reduction, triangulation, data presentation). This research was carried out in the SD Negeri 14 Buton environment for the 2020/2021 academic year. The results of the study show that the character of students at SD Negeri 14 Buton tends to have positive characters, this can be proven by the character values that are applied, trained, and given examples by teachers so that they have good character, besides that the school environment is very influential on character building of students at SD Negeri 14 Buton. This can be seen from the method used to foster better character changes, among others, by applying student character values consisting of religious, disciplined, and caring characters for the environment.